Palmistichus elaeisis (Hymenoptera: Eulophidae) parasitizing pupae of Citioica anthonilis (Lepidoptera: Saturniidae) collected on Piptadenia gonoacantha (Fabaceae) - Tavares, Wagner de Souza; Hendrik Mielke, Olaf Hermann; Wilcken, Carlos Frederico [UNESP]; Simon, Leroy; Serrao, Jose Eduardo; Zanuncio, Jose Cola (Lepidopterists Soc, 2012)
The moth Citioica anthonilis (Herrich-Schaeffer, [1854]) (Lepidoptera: Saturniidae: Ceratocampinae) occurs in areas of preserved forests, where it is a significant defoliator of Piptadenia gonoacantha (Martins) Macbride (Fabaceae) trees. In this study, caterpillars of fourth instar C. anthonilis were collected from the ground after falling from a P gonoacantha tree in a herbarium and were reared in the laboratory. Pupae of C. anthonilis, the velvetbean caterpillar Anticarsia gemmatalis Hubner, 1818 (Lepidoptera: Noctuidae), and the flour beetle Tenebrio molitor Linnaeus, 1758 (Coleoptera: Tenebrionidae) were each parasitized by mated parasitoid females wasp Palmistichus elaeisis Delvare & LaSalle, 1993 (Hymenoptera: Eulophidae). Data were collected relating to the levels of parasitism and emergence rates of P. elaeisis per host pupa, and the size of the host pupae. Our results show that the fecundity of P. elaeisis was highest in C. anthonilis hosts, probably because of the greater size of these pupae, which supported the development of an increased number of parasitoids. Therefore, C. anthonilis is a suitable host for rearing P elaeisis in the laboratory, which could be a means of rearing parasitoids for the biological control of this defoliator of P. gonoacantha and other pests in Brazil.
Keywords: biological control; forest insects; host; parasitism; pupal parasitoid